1999
DOI: 10.1042/0264-6021:3410315
|View full text |Cite
|
Sign up to set email alerts
|

Upstream stimulatory factor regulates Pdx-1 gene expression in differentiated pancreatic β-cells

Abstract: The homeobox gene Pdx-1 plays a key role in the development of the pancreas. In the adult, however, expression of the Pdx-1 gene is restricted to pancreatic beta-cells and endocrine cells of duodenal epithelium. Recently, the transcription factor, upstream stimulatory factor (USF), has been shown to bind in vitro to a mutationally sensitive E-box motif within the 5'-flanking region of the Pdx-1 gene [Sharma, Leonard, Lee, Chapman, Leiter and Montminy (1996) J. Biol. Chem. 271, 2294-2299]. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…Inspection of the DNA sequence of the EB1 element revealed that it fits the preferred site for binding by the bHLH transcription factors USF1 and USF2 [29]. Expression of USF1 and USF2 in RC2.E10, MIN6 and primary MEM cells was confirmed by Western blot analysis ( Figure 3A).…”
Section: Usf1 and Usf2 Specifically Bind To Eb1mentioning
confidence: 71%
“…Inspection of the DNA sequence of the EB1 element revealed that it fits the preferred site for binding by the bHLH transcription factors USF1 and USF2 [29]. Expression of USF1 and USF2 in RC2.E10, MIN6 and primary MEM cells was confirmed by Western blot analysis ( Figure 3A).…”
Section: Usf1 and Usf2 Specifically Bind To Eb1mentioning
confidence: 71%
“…10A) (32,33). Considering the critical importance of the E-box, but modest stimulation of the Pdx-1 promoter by USF1 cotransfection (data not shown), it has been speculated that the action of USFs is mediated in synergy with another factor (33). Our data indicate that PDX-1 directly binds to USF1 and contributes to the transactivation of the Pdx-1 promoter.…”
Section: Discussionmentioning
confidence: 65%
“…USFs play a key role in the transcription of pdx-1 through this E-box (Fig. 10A) (32,33). Considering the critical importance of the E-box, but modest stimulation of the Pdx-1 promoter by USF1 cotransfection (data not shown), it has been speculated that the action of USFs is mediated in synergy with another factor (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations